2020
DOI: 10.32098/mltj.03.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Post-Stroke Biceps Brachialis Muscle Stiffness by Shear-Wave Elastography: a Pilot Study

Abstract: Objectives. Spasticity following stroke tend to increase muscle stiffness. Recent clinical measures of post-stroke biceps brachialis muscle spasticity are subjective. We aimed to measure post-stroke biceps brachialis muscle stiffness quantitatively by using shearwave elastography (SWE). Methods. This prospective study included 24 post-stroke patients with unilateral biceps brachialis muscle spasticity. The Modified Ashworth Scale of the biceps muscle, Brunnstrom stages of the upper extremity of the patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The quick-stretch technique is a simple way to induce spasticity. However, previous studies have suggested that using this technique may lead to insufficient repeatability and efficacy [11] , [13] [16] . The ACMES uses a robotic-type design that can continuously produce steady motion and speed that will allow simulation of the same quick-stretch every time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quick-stretch technique is a simple way to induce spasticity. However, previous studies have suggested that using this technique may lead to insufficient repeatability and efficacy [11] , [13] [16] . The ACMES uses a robotic-type design that can continuously produce steady motion and speed that will allow simulation of the same quick-stretch every time.…”
Section: Discussionmentioning
confidence: 99%
“…For clinicians, a proper assessment that can be used to quantify muscle tone, especially abnormal muscle tone, is always an important issue that must be done before applying suitable interventions. Although the quick-stretch technique is an easy, common strategy by which clinicians can induce abnormal muscle tone, and the MAS assessment is widely used clinically as well, the inconsistency of the force applied from the examiners and the subjective scoring are concerns that should not be ignored [11] , [13] [16] . To solve the problems related to the current muscle tone scoring system, previous researchers have used EMG, torque, or force sensors to quantify muscle tone [10] , [12] , [17] [27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future implications of this study include studying the AcBr in vivo by using ultrasound, MRI and electromyogram methods. Elastography is a newly established North American based technique to assess the tissue stiffness (26). The AcBr can be studied in vivo by using elastography and the stiffness of the arm can be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The AcBr can be studied in vivo by using elastography and the stiffness of the arm can be evaluated. Analan and Ozdemir (26) reported that, neurological disorders are not the only etiological factors for the muscle stiffness, few more factors like anatomical variations, posture, gender and exercise also have a role.…”
Section: Discussionmentioning
confidence: 99%